Persepsi Mahasiswa MIPA Terhadap Pengelolaan Sampah Padat Berbasis 3R Di Kampus Universitas Islam Malang - Ahmad Taufiq Rohman; Ari Hayati; Ratna Djuniwati Lisminingsih (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2023)
According to the republic of indonesia no undang-undang 18 years 2008, about waste management waste matter especially in kota-kota throughout the country right now this has been an issue that is always discussed the need to get the attention of all parties, no exception to the environment, poor islamic university campus how students perception about waste management 3r, based how about the model student perception of the trash can exist at community college islamic university, poor how are the awareness of student participation environmental quality to maintain a healthy and clean through waste management 3r, based this research use descriptive quantitative research methods and surveys in a field. directly A survey is data collection techniques specific techniques, than the other the percentage of perception student who answered a questionnaire in rata-rata show high marks, Student perception about waste management 3r based in college islamic university shows poor perception is very high obtained the results of ( 83-86 % ), a student knowing and perceiving a model that dumpster in the islamic university campus menunujuk very high percentage of poor showing the perception is very high obtained the results of ( 83-85 % ), the awareness of the students faculty mipa against participation menunujuk very high percentage of these things that indicated the result of ( 80-89 % )